Impact of transcription factor Sox8 on oligodendrocyte specification in the mouse embryonic spinal cord. - Sock, Elisabeth; Wegner, Michael; Stolt, Claus; et al. (Developmental Biology, 2005)
The myelin-forming oligodendrocytes of the mouse embryonic spinal cord express the three group E Sox proteins Sox8, Sox9, and Sox10. They require Sox9 for their specification from neuroepithelial cells of the ventricular zone and Sox10 for their terminal differentiation and myelination. Here, we show that during oligodendrocyte development, Sox8 is expressed after Sox9, but before Sox10. Loss of Sox8 did not impair oligodendrocyte specification by itself, but enhanced the Sox9-dependent defect. Oligodendrocyte progenitors were still generated in the Sox9-deficient spinal cord, albeit at 20-fold lower rates than in the wildtype. Combined loss of Sox8 and Sox9, in contrast, led to a near complete loss of oligodendrocytes. Other cell types such as ventricular zone cells and radial glia remained unaffected in their numbers as well as their rates of proliferation and apoptosis. Oligodendrocyte development thus relies on the differential contribution of all three group E Sox proteins at various phases. © 2005 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.med.IB.LPCIPDBI.impact
Keywords: Glia; High-mobility-group; Knockout; Oligodendrogenesis; Redundancy; Sox10; Sox9; Sry